The future of cardiovascular magnetic resonance imaging in thoracic aortopathy: blueprint for the paradigm shift to improve management - James Nadel; José Rodríguez-Palomares; Alkystis Phinikaridou; Claudia Prieto; Pier-Giorgio Masci; René Botnar (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Thoracic aortopathies result in aneurysmal expansion of the aorta that can lead to rapidly fatal aortic dissection or rupture. Despite the availability of abundant non-invasive imaging tools, the greatest contemporary challenge in the management of thoracic aortic aneurysm (TAA) is the lack of reliable metrics for risk stratification, with absolute aortic diameter, growth rate, and syndromic factors remaining the primary determinants by which prophylactic surgical intervention is adjudged. Advanced cardiovascular magnetic resonance (CMR) techniques present a potential key to unlocking insights into TAA that could guide disease surveillance and surgical intervention. CMR has the capacity to encapsulate the aorta as a complex biomechanical structure, permitting the determination of aortic volume, morphology, composition, distensibility, and fluid dynamics in a time-efficient manner. Nevertheless, current standard-of-care imaging protocols do not harness its full capacity. This state-of-the-art review explores the emerging role of CMR in the assessment of TAA and presents a blueprint for the required paradigm shift away from aortic size as the sole metric for risk-stratifying TAA.